Adaptive Arc Detection Based Image Segmentation in Pantograph Catenary Systems - Karaköse, Mehmet; Yaman, Orhan; Aydın, İlhan; Akın, Erhan (Akademik Bilişim Vakfı [EN], 2017)
In recent years, through the development of electric trains, the rail system has become a popular mode of transport. This type of transport is reliable and cost-effective compared to other modes of transport. Furthermore, the rail transport is more preferred with the emergence of the electric train.  In order to provide the electrical energy used by electric trains, pantograph catenary system was developed. Pantograph system, receives power from the catenary wire and transmits to train. The catenary system, located along the railway line, it transmits electricity from the substation to the pantograph system. During contact with pantograph and catenary system many failures may occur. Early diagnosis of failures are preventing larger defect.  In this study, a new image processing based method for arc detection in pantograph catenary system, which is a part of the rail system, is proposed.  Real-time images of the catenary pantograph is taken by cameras placed on the roof of two different locomotives. The image segmentation is used to identify the differences that occur in images taken. Also, the Sobel edge extraction algorithm is used for detecting contact of a pantograph. The arcing at the contacts of the pantograph is determined by combining properties obtained. The proposed method has been carried out both in the FPGA environment MATLAB and the results were compared.

Son yıllarda elektrikli trenlerin gelişmesiyle birlikte raylı sistemler popüler bir ulaşım türü haline gelmiştir. Bu ulaşım türü diğer ulaşım türlerine göre düşük maliyetli ve güvenilirdir. Ayrıca elektrikli trenlerin ortaya çıkmasıyla birlikte demiryolu ulaşımı daha çok tercih edilmiştir. Elektrikli trenlerin kullandığı elektrik enerjisinin temin edilmesi için pantograf katener sistemleri geliştirilmiştir. Pantograf sistemi, trenin üzerinde bulunan katener telinden aldığı elektriği trene ileten sistemdir. Katener sistemi ise, demiryolu hattı boyunca bulunur ve trafo merkezinden alınan elektriği pantograf sistemine iletmektedir. Pantograf ve katener sistemlerinin birbiri ile teması sırasında çeşitli arızalar ortaya çıkmaktadır. Oluşan arızaların erken teşhis edilmesi daha büyük arızaların oluşmasını engellemektedir. Bu çalışmada, raylı sistemlerin bir parçası olan pantograf katener sistemlerde ark tespiti için görüntü işleme tabanlı yeni bir yöntem önerilmektedir. İki farklı lokomotifin çatısına kamera yerleştirilerek pantograf katener sisteminin gerçek zamanlı görüntüsü alınmıştır. Alınan görüntülerde oluşan arkların tespiti için görüntü segmantasyonu kullanılmıştır. Ayrıca pantograf temas bölgesinin tespit edilmesi için Sobel kenar çıkarım algoritması kullanılmıştır. Elde edilen özellikler bileştirilerek pantograf temas bölgesinde oluşan arkların tespiti yapılmaktadır. Önerilen yöntem hem MATLAB hem de FPGA ortamında gerçekleştirilmiştir ve sonuçları karşılaştırılmıştır.
Pantograf Katener Sistemlerde Görüntü Segmantasyon Tabanlı Adaptif Ark Tespiti
Keywords: Engineering; Mühendislik